Ultra‐small and highly dispersed Pd nanoparticles inside the pores of ZIF‐8: Sustainable approach to waste‐minimized Mizoroki–Heck cross‐coupling reaction based on reusable heterogeneous catalyst. (8th May 2019) - Azad, Mohammad; Rostamizadeh, Shahnaz; Estiri, Hamid; Nouri, Fatemeh
Abstract : The rapid development of nanomaterials, particularly advanced hybrid nanoparticles, has made new opportunities for the design and fabrication of high‐performance metal‐based catalysts. However, generating metal nanoparticles of desired size without aggregation is an important challenge for enhancing the catalytic activity of metal nanoparticles supported in the host matrix. In this work, a hybrid nanoporous material, namely Pd nanoparticles@N‐heterocyclic carbene@ZIF‐8, with a high internal surface area was successfully prepared using a dispersed anionic sulfonated N‐heterocyclic carbene–Pd(II) precursor inside the cavities of zeolitic imidazolate framework (ZIF‐8) using an impregnation approach followed by reduction with NaBH4 . The anionic sulfonated N‐heterocyclic carbene was found to be a superb ligand for the stabilization of Pd nanoparticles in the pores of ZIF‐8. The resulting system was applied to the Mizoroki–Heck cross‐coupling reaction, in which the catalyst showed high catalytic activity under mild reaction conditions. Abstract : The use of a heterogeneous catalyst has become an efficient route for improvement of green chemistry. Pd nanoparticles@N‐heterocyclic carbene@ ZIF‐8 (Pd NPs@NHC@ZIF‐8), with a high internal surface area was successfully prepared by dispersed anionic sulfonated N‐heterocyclic carbene‐ palladium (II) precursor inside the cavities of zeolitic imidazolate framework (ZIF‐8). The resulted system was applied to the Mizoroki–Heck cross‐coupling reaction; in which the catalyst showed high catalytic activity under mild reaction conditions.